From TPACK to N-TPACK framework for vocational education and training with a focus on nutritional science and home economics - Carmen Torggler; Susanne Miesera; Claudia Nerdel (International Journal for Research in Vocational Education and Training (IJRVET), 2023)
Context: In Germany, vocational education and training (VET) plays a key role in the transition from school to working life. Due to its proximity to the labour market and an increasingly digitised, connected world, the professional knowledge requirements of VET teachers are changing and an adjustment of competence frameworks for vocational teachers is needed. Approach: Since its introduction, the TPACK (Technological Pedagogical And Content Knowledge) framework of Shulman and Mishra and Koehler has been repeatedly used in the international research discourse as a framework for capturing teachers' professional knowledge. Given the infrequent reference to TPACK in the field of vocational education and training (VET), this theoretical article aims to adapt the TPACK framework for VET teachers. A literature review revealed the importance of developing an adapted TPACK framework that takes into account the peculiarities of the German vocational school system as well as the non technical personal service sector. Based on this research gap, an appropriately adapted TPACK framework was developed. The focus of this article lies on VET of nutritional science and home economics. Findings: After considering and analysing the requirements of the VET system in Germany in the context of digitalisation, it is suggested to adapt and enlarge the existing TPACK framework, thus creating an N-TPACK framework, taking into account "Networking and Collaborative Knowledge (NK)" as an aspect of essential VET teachers' professional knowledge. Conclusion: The present theoretical article considers the research desideratum of extending the TPACK framework by developing a theoretical N-TPACK framework as well as examining and discussing the various knowledge areas. Building on this theoretical article, a survey of the current status quo of these professional knowledge areas among (prospective) VET teachers in the subject area of nutrition and home economics is necessary, in order to provide orientation and to be able to derive recommended actions for an up-to-date and forward looking teacher education and training.
urn:nbn:de:gbv:18-10-1077-3
Keywords: 330; Vocational Education and Training; VET; Digitalisation; Vocational Teachers; Skills and Knowledge